Psychological Aspects Associated With Fertility Preservation in Oncology: An Exploratory Study - Di Mattei, Valentina Elisabetta; Perego, Gaia; Rancoita, Paola Maria Vittoria; Taranto, Paola; Carnelli, Letizia; Mangili, Giorgia; Sarais, Veronica; Bergamini, Alice; Candiani, Massimo (Frontiers in Psychology, 2020)
Objective: Gonadotoxicity is considered one of the most distressing side effects of cancer treatment. Although fertility preservation can be a valid solution, it also involves a challenging process. A clear understanding of the features of women who decide to pursue fertility preservation after cancer diagnosis is missing. The purpose of the present study was therefore to analyze the personality profile of female patients referred to oncofertility prior to gonadotoxic treatment. Methods: Fifty-two female cancer patients took part in the study. The Temperament and Character Inventory-Revised (TCI-R), the Response Evaluation Measure – 71 (REM-71), the Beck Depression Inventory (BDI-II), and the State-Trait Anxiety Inventory-Y Form (STAI-Y) were administered to examine personality characteristics, defense mechanisms, depression and anxiety symptoms. Results: Compared with reference data of the Italian population, our sample reported significantly lower scores in Harm Avoidance and trait anxiety, and significantly higher levels of mature defense mechanisms. Most of the patients reported low scores in immature defense mechanisms, depression, and trait anxiety, and medium scores in state anxiety. Conclusions: Our findings suggest that these women display functional personality traits and defensive style, in association with low levels of depression and trait anxiety. These features may enable a proactive attitude to cancer and the ability to make long-term plans. This may favor psychological adjustment to cancer and a projection towards the future.